APPROACH TO INTEGRATIVE MASTER HEALTH CHECK COMBINING HEALTH SCREENING PARAMETERS OF AYURVEDA AND BIOMEDICINE – A NARRATIVE REVIEW - Vivek Sanker MK,; Naidu MUR,; Gangadharan GG, (International Journal of Ayurveda and Pharma Research, 2020)
Health check-up is an annual program that attempts to reduce health care costs by early detection of disease symptoms before its usual clinical presentation that can encourage adoption of preventive measures or early treatment. There is a concern among clinicians that the standard tests under health screening packages could be off target in terms of detection of relevant symptoms as far as a few individual groups are concerned and end-up in wastage of money of the end customer. The article presents a review of the current evidences for and against screening of healthy volunteers enlists some of the key challenges that have been reported in health check-up programs and argues the need to give individualized advice on diet and lifestyle through suitable integration of concepts of Ayurveda. It outlines the components of an integrated health screening parameter developed from the ten-fold clinical examination procedure recommended in Ayurveda (called Dasavidhapareeksha) and argues the case for critically drawing from the strengths of both systems of medicine.